(untitled) (Symposium on Life and Environmental Sciences, 2026)
This thesis studies the hydrolysis of the aluminium and iron(III) salts within the composite coagulant, the formation of polynuclear hydroxo-complexes and their coagulation activity. Hydrolysis is multistage and develops from mononuclear hydroxo-complexes to polynuclear species, in particular the Keggin structure Al₁₃O₄(OH)₂₄(H₂O)₁₂⁷⁺ (Al₁₃). By the Ferron method the species were resolved into mononuclear (Al_a), polynuclear (Al_b) and colloidal-precipitate (Al_c) fractions. The polynuclear Al₁₃ fraction exhibited the highest coagulation activity, since its high positive charge and size combine charge neutralisation with bridging. At a basicity B = [OH]/[Me] ≈ 1.8–2.2 the Al₁₃ content was maximal (≈ 70 %) and turbidity removal reached 96.4 %. The results justify the advantage of pre-hydrolysed reagents.